2010
DOI: 10.1021/ja1047736
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Photocleavage of a Monochromophoric Linker

Abstract: The 4-acetyl-2-nitrobenzyl moiety, substituted in both benzylic and phenacyl positions with leaving groups, has been proposed as a monochromophoric photocleavable linker. The attached groups can be disconnected selectively and orthogonally upon irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
1
35
0
2
Order By: Relevance
“…48 This linker thus combines the properties of two well-known photoremovable groups, 2-nitrobenzyl (section 3.1) and phenacyl moieties, in a single chromophore. Liberation of R′CO 2 H from the intermediate 2 requires the presence of an H-atom donor.…”
Section: Arylcarbonylmethyl Groupsmentioning
confidence: 99%
“…48 This linker thus combines the properties of two well-known photoremovable groups, 2-nitrobenzyl (section 3.1) and phenacyl moieties, in a single chromophore. Liberation of R′CO 2 H from the intermediate 2 requires the presence of an H-atom donor.…”
Section: Arylcarbonylmethyl Groupsmentioning
confidence: 99%
“…[3] Excited-state hydrogen transfer (ESHT), a process that stood at the origin of modern photochemistry, [2a] plays an essential role in the functionality of many chemical and biological systems. In particular, the phototautomerization of o-nitrobenzyl (oNB) derivatives 1 [4] results in a cascade of irreversible reactions that lead to the ejection of leaving groups (LGs) X (Scheme 1), a reaction that has found numerous applications in photoactivatable ("caged") compounds in chemistry, [5] biochemistry, [6] macromolecular [7] and neural sciences, [8] photolithography, [9] or the fabrication of DNA chips. [10] It has been shown that photoexcitation of 1 is followed by rapid (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently it is not the nucleofugacity, since quantum yields for the decay of the 4-acetyl-2-nitrobenzyl protected benzylalcohol in methanol was found to be 0.88 while it was only 0.051 for the corresponding phenylacetic acid. 29 In this paper we propose a simple predictive model to explain a series of quantum yields for the release of seven different commonly used leaving groups from o-nitroveratryl PPGs. Based on a minimal mechanistic scheme, these values are correlated with a measure that can be evaluated easily using standard quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%